Viabundus: Map of Premodern European Transport and Mobility (Research Data Journal for the Humanities and Social Sciences, 2022)
Viabundus is an open access online interactive map and database on roads and mobility in premodern northern and central Europe. The database covers the period 1350–1650. It is designed as a network model and includes digital reconstructions of long-distance land routes and inland waterways as well as a database with information about settlements, towns, toll stations, staple markets, fairs, bridges, ferries, harbours and shipping locks. This makes it possible to use the dataset for advanced analyses with methods of gis and network analysis. With the web application and downloadable dataset, the Viabundus project has created a tool for the analysis of premodern mobility for economic (transaction costs) and all other kinds of historical study involving movement of people and goods.